Determinasi angka harapan hidup: Analisis pada enam kota di Provinsi Jawa Tengah tahun 2018–2023 - Nuha, Auziqna Fadli Rosihan; Nurhayati, Siti Fatimah (Nur Science Institute, 2025)
Life expectancy figures for six cities in Central Java face challenges from time to time. This research aims to analyze the factors influencing life expectancy in 6 cities in Central Java province. Factors thought to influence are GRDP, inflation, minimum wage, and a number of health facilities. The data analysis method used is panel data regression. The results of selecting the best model show that the Random Effect Model is the best model selected. The results show that the GRDP, minimum wage and a number of health facilities variables positively affect life expectancy. In contrast, the inflation variable is proven to not affect life expectancy.